2012
DOI: 10.4049/jimmunol.1201271
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for CD70 and CD80/CD86 in Dendritic Cell-Mediated Activation of Tumor-Tolerized CD8 T Cells

Abstract: A major obstacle to efficacious T cell-based cancer immunotherapy is the tolerizing tumor microenvironment that rapidly inactivates tumor-infiltrating lymphocytes. In an autochthonous model of prostate cancer, we have previously shown that intratumoral injection of antigen loaded dendritic cells (DCs) delays T cell tolerance induction as well as refunctionalizes already tolerized T cells in the tumor tissue. In this study, we have defined molecular interactions that mediate DCs’ effects. We show that pretreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…These results suggest that CD4 T cells play a more dominant role in the PLX4720-mediated anti-tumor response than CD8 T cells. Note, we also examined whether the elevated CD70 expression on APCs after PLX4720 therapy contributed to its ability to reverse tolerant CTLs and retard tumor growth (14, 15, 34), but found that blocking CD70 did not perturb the ability of PLX4720 to inhibit tumor progression in any detectable manner (Supplementary Figure 6). …”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that CD4 T cells play a more dominant role in the PLX4720-mediated anti-tumor response than CD8 T cells. Note, we also examined whether the elevated CD70 expression on APCs after PLX4720 therapy contributed to its ability to reverse tolerant CTLs and retard tumor growth (14, 15, 34), but found that blocking CD70 did not perturb the ability of PLX4720 to inhibit tumor progression in any detectable manner (Supplementary Figure 6). …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, expression of CD70 on tumor cells or antigenpresenting cells has also been described to have anti-tumoral effects (Arens et al, 2004;Bak et al, 2012;Couderc et al, 1998;Glouchkova et al, 2009;Kelly et al, 2002;Lorenz et al, 1999). This raises the question if CD70 blocking antibodies might also have the opposite effect on anti-tumoral immunity by blocking the stimulatory function of CD70 on antigen-presenting cells and NK cells or by depleting activated T cells, as suggested by the CD27-agonistic antibody, CDX-1127 (Thomas et al, 2014).…”
Section: Discussion: Are We Targeting the Right Molecule?mentioning
confidence: 98%
“…S7B). Many of these genes have been shown to be critical for antitu-mor responses, including those involved in CD8 + T cell activation and costimulation [ H2-m2 (MHC-I), Cd40 , Cd70 , and Icam1 ] (20–22); DC maturation ( Relb and Ifngr2 ) (23, 24); antigen processing and cross presentation ( Tapbp , Rab27a , and Slc11a1 ) (2527); chemokine-mediated recruitment of immune cells to the tumor microenvironment ( Cxcl9 , Cx3cl1 , and Cxcr4 ) (2830); and type I interferon signaling ( Irf1 , Ifnar2 , Oas2 , Ifi35 , and Ifitm1 ) (31, 32) (Fig. 4D and fig.…”
mentioning
confidence: 99%